South European undergraduate and continuing professional development program reconceptualization for the New Information Professional: a synergistic innovation perspective - Sant-Geronikolou , Stavroula (Journal of Integrated Information Management, 2024)
Purpose – As, under the new educational, communicational and technological paradigms, Library and Information Science curricula reconceptualization is gaining momentum, this opinion paper should be seen as a theoretical contribution to current thinking around South European formal education and Continuing Professional Development potential to effectively addressing the New Academic Library challenges. Design/methodology/findings - Building on context-specific case studies and previous international research focusing the investigation of the necessity to reshape official undergraduate programs and academic librarian career-long learning opportunities, our paper discusses whether and how an open flexible synergistic approach could be an ideal solution to current scenario pain points. Besides offering a brief but comprehensive review of the topic, it further proposes a set of future research studies that may result foundational to change within the librarian community by helping unpack the complexities of an ecosystem still in search of its identity.